Polish cooperative banks as net lenders in the money market - Maria Magdalena Golec; Piotr Płuciennik (e-Finanse: Financial Internet Quarterly, 2017)
Due to the traditional operational model of cooperative banks which is mostly based on financial intermediation, the range of a local bank's social influence in a given environment is highly dependent on the money transfer balance, that is using local money to satisfy local needs. A typical obstacle to this activity could be observed in Poland, in positive money transfers in those banks understood as the excess of deposits from customers over loans given to them. The purpose of the following paper is to examine this phenomenon in Polish cooperative banks in comparison to credit cooperatives in Europe together with its explanation on the basis of the selected group of cooperative banks in Poland. According to the sector data in the years 2004-2015 Polish cooperative banks are net lenders for the remaining entities of the financial sector. On the European market, on the other hand, groups of cooperative banks aim to balance money transfers. It is the activity of the biggest sector players that mostly influences the information concerning credit cooperatives, which is why more thorough research into the group of over 90 Polish cooperative banks was conducted in the years 2009-2016. In the examined group deposits exceed loans and the phenomenon continues to grow and it has been observed in over three quarters of the institutions in question since 2011.
Keywords: G21; M21; L31; 330; cooperative bank; money transfers; deposits; loans